NEW PROTEROCHAMPSID SPECIMENS EXPAND THE MORPHOLOGICAL DIVERSITY OF THE RHADINOSUCHINES OF THE CHAÑARES FORMATION (LOWER CARNIAN, NORTHWESTERN ARGENTINA) (Ameghiniana, 2019)
The proterochampsids are crocodile-like, small- to medium-sized, quadrupedal and predatory stem-archosaurs. The rhadinosuchines are a clade of deeply nested proterochampsids that are the most abundant diapsids of the Massetognathus-Chanaresuchus Assemblage Zone of the Chañares Formation (lower Carnian) of north-western Argentina. Here, we describe two new rhadinosuchine proterochampsid specimens recently collected from the Massetognathus-Chanaresuchus Assemblage Zone of the Chañares Formation. These specimens are represented by an articulated partial skeleton and disarticulated cranial and postcranial bones, respectively. One of them is less complete, but its well-preserved disarticulated bones considerably expand the anatomical knowledge of certain regions of the rhadinosuchine skeleton. The combination of character-states present in both specimens and shared with other known rhadinosuchine species (e.g., Chanaresuchus bonapartei, Gualosuchus reigi, Rhadinosuchus gracilis) results in an unexpected increase of the morphological diversity of the group (e.g., antorbital fossa on the horizontal process of maxilla, well-exposed antorbital fossa on lacrimal, X-shaped osteoderms). We conclude that the taxonomy of the currently known rhadinosuchine specimens should be revisited, including a careful reappraisal of the intraspecific variation and the post-mortem deformation that affected the specimens in different ways.